Public relations: The empirical research on practitioner ethics - Pratt, Cornelius B. (Journal of business ethics, 1991)
An examination of the empirical literature on public relations ethics indicates serious doubts and concerns about the ethics of the public relations practice. Practitioners tend to perceive the ethics of their top management as higher than their own ethics, suggesting that top management (of which practitioners are a part) should be in the forefront of improving organizational and practitioner ethics., This article also discusses public relations practitioners' suggestions on how ethics in public relations can be improved. Sample members of the Public Relations Society of America most frequently suggest having ethics education, taking disciplinary action against violators of codes of ethics, and emphasizing professionalism of practitioners as strategies for improving practitioner ethics. This article also concludes that, because ethics education leads the list of suggestions, professional-development seminars and college-level courses might explore in further detail those ethics issues most common in the practice and might examine in group settings how the ethics of such issues are perceived by practitioners.